SOLVING THE HYPERBOLIC PROBLEM OBTAINED BY TRANSMUTATION OPERATOR - Koyunbakan, Hikmet (Nova Science Publishers, Inc, 2009)
In this paper, we solve the problem of constructing the kernels of transmutation operator and give the generalized transmutation operator for a singular problem.
Keywords: Inverse Problem; Hyperbolic Equation